EFL Teachers’ English Language Use During the Pandemics in the Indonesian Senior High School Context - Saleh, Asmaul (Pascasarjana Universitas Negeri Makassar, 2023)
In response to the significant upheaval caused by the global pandemic, education systems worldwide have shifted from traditional classroom settings to remote teaching methods. This drastic transition has presented numerous challenges, particularly in the realm of English as a Foreign Language (EFL) education in non-English speaking countries, such as Indonesia. This study embarks on an in-depth exploration of how the teaching methodologies and language functions utilized by EFL teachers at an Indonesian senior high school, MAN 2 Parepare, have adapted to these new learning environments. The research adopts a descriptive qualitative research design, providing a comprehensive view of the phenomena under investigation. The in-depth investigation focuses on the practices of two English teachers at MAN 2 Parepare, analyzing the way they employ different language functions during their online classes. The analysis seeks to elucidate the interaction between instructional language and the online learning environment, how it affects student comprehension, and the potential for instructional refinement. Findings indicate a broad range of language functions used by both teachers in their instructional strategies, demonstrating the adaptive potential of EFL instruction under the pressures of pandemic-induced remote teaching. Notably, the study reveals that the use of students' native language and the target language - English - plays a crucial role in aiding students' comprehension, highlighting the importance of maintaining a balance between the two. In sum, this paper offers valuable insights into the language function dynamics at play in online EFL classrooms during the pandemic. The findings have implications for informing instructional best practices and contribute to the broader understanding of language education in a rapidly changing global context.